2013
DOI: 10.1504/ijptech.2013.057055
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of micro and nano-scale defects with WVTR for aluminium oxide barrier coatings for flexible photovoltaic modules

Abstract: This paper seeks to establish a correlation between surface topographical defects and Water Vapour Transmission Rate (WVTR) measured under laboratory conditions for aluminium-oxide (Al 2 O 3) barrier film employed in flexible photovoltaic (PV) modules. Defects in the barrier layers of PV modules causing high WVTR are not well characterised and understood. A WVTR of ~10-1 g/m 2 /day is sufficient for the most packaging applications, but ≤10-6 g/m 2 /day is required for the encapsulation of long-life flexible PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…(5) and (6) for the given sets of parameters and variables for each sample, as shown in Appendix A(1), and substituting all the known data (sample area, sample thickness, number of defects, diffusion coefficient, water vapour concentration and the accumulative area of the defects) into Eq. (6), the theoretical model based on the approach of Da Silva Sobrinho et al [11] led to results which are similar to those obtained by surface topography analysis [36,37] and experimental WVTR test results. Calculations are shown in Appendix A(1).…”
Section: Wvtr Analysis and Results Discussionsupporting
confidence: 69%
“…(5) and (6) for the given sets of parameters and variables for each sample, as shown in Appendix A(1), and substituting all the known data (sample area, sample thickness, number of defects, diffusion coefficient, water vapour concentration and the accumulative area of the defects) into Eq. (6), the theoretical model based on the approach of Da Silva Sobrinho et al [11] led to results which are similar to those obtained by surface topography analysis [36,37] and experimental WVTR test results. Calculations are shown in Appendix A(1).…”
Section: Wvtr Analysis and Results Discussionsupporting
confidence: 69%
“…The WVTR of a barrier film can be much higher than the intrinsic WVTR of the barrier material when the barrier film has pinholes and macroscopic defects because such defects act as accelerated gas diffusion paths [5,9,45]. It was observed that few large defects contributed most of the permeation [46]. To investigate the effect of 2LG on barrier property under tensile deformation, WVTR measurements were performed on Al 2 O 3 /PI and Al 2 O 3 /2LG/PI after the tensile tests, up to a tensile strain of 3%.…”
Section: Wvtr Measurements After Tensile Deformationmentioning
confidence: 99%
“…The relationship between the surface morphology, defect density, and water vapor permeability through 40 nm Al 2 O 3 barrier coatings produced using ALD [3] on 125-μm polyethylene naphthalate (PEN) substrates has to date only been studied in a laboratory [4,5]. However, detecting defects off-line is difficult and time consuming.…”
Section: Challenges In Defect Detectionmentioning
confidence: 99%
“…Moreover, segmentation analysis results [5,13] appear to indicate that the major contributing factor for determining the WVTR is the total number of larger defects, where a sample with a higher density of defects of greater than 3 μm in lateral dimension and a 3 × Sq vertical dimension exhibits inferior barrier properties. These criteria are considered to be the basis for developing the segmentation "toolbox" shown in Fig.…”
Section: Wsi Data Handling Proceduresmentioning
confidence: 99%